2016
DOI: 10.1007/s11356-016-6504-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of indoor climate of Mogiła Abbey in Kraków (Poland) and the application of the analogues method to predict microclimate indoor conditions

Abstract: The microclimatic monitoring of the historic church of Mogiła Abbey (Kraków, Poland) was carried out to study the impact of the environmental parameters on the organic and hygroscopic artworks. Specific indexes were proposed to objectively assess the quality of time series of temperature (T), relative humidity (RH), and carbon dioxide (CO) before applying the exploratory data analysis. The series were used to define the historic environmental conditions as stated in the European Standard EN 15757:2010 and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The results obtained by considering two churches (Church of Rocca Pietore in Italy and Church in Szalowa, Poland) have shown that all heating systems tend to re-suspend the particulate matter brought in from outside; however, the extent changes in relation to the chosen system. Frasca et al [21] presented the assessment of indoor climate conditions of the Basilica of the Holy Cross in Mogiła Abbey at Cracow (Poland) by experimentally measuring temperature, relative humidity and carbon dioxide in the period between March 2012 and April 2014. They found that 15% of the time, temperature and relative humidity did not meet the limits proposed by ASHRAE Class B and, therefore, during this time there was a high risk that the artworks preserved in the church (mostly wooden artworks) were subject to mechanical damage, especially due to relative humidity fluctuations.…”
Section: Related Workmentioning
confidence: 99%
“…The results obtained by considering two churches (Church of Rocca Pietore in Italy and Church in Szalowa, Poland) have shown that all heating systems tend to re-suspend the particulate matter brought in from outside; however, the extent changes in relation to the chosen system. Frasca et al [21] presented the assessment of indoor climate conditions of the Basilica of the Holy Cross in Mogiła Abbey at Cracow (Poland) by experimentally measuring temperature, relative humidity and carbon dioxide in the period between March 2012 and April 2014. They found that 15% of the time, temperature and relative humidity did not meet the limits proposed by ASHRAE Class B and, therefore, during this time there was a high risk that the artworks preserved in the church (mostly wooden artworks) were subject to mechanical damage, especially due to relative humidity fluctuations.…”
Section: Related Workmentioning
confidence: 99%
“…The long time series of microclimate data that were collected over the years were objectively evaluated with the Completeness Index (CoI) and the Continuity Index (CI), defined in [27], in order to assess the quality of the datasets before applying data analysis.…”
Section: Microclimate Data Analysismentioning
confidence: 99%
“…Many studies have been conducted in recent years which monitor the climatic parameters for the long-term preservation of cultural heritage. Frasca et al [ 14 ] studied the impact of T, RH and carbon dioxide (CO ) on the organic and hygroscopic artworks in the church of Mogiła Abbey. They found that artworks were at high risk of mechanical damage for approximately 15% of the time under study, due to an excessive variability of RH.…”
Section: Introductionmentioning
confidence: 99%